KONSENTRASI LOGAM BERAT (Pb, Cd, Cu, Zn) TERLARUT, DALAM SESTON, DAN DALAM SEDIMEN DI ESTUARI BANJIR KANAL BARAT, SEMARANG - LILIK MASLUKAH (Akuatik: Jurnal Sumberdaya Perairan, 2007)
Trace metals in the aquatic environment are formed either in dissolved or particulate fractions. Within an estuary, the metals are influenced by dilution, adsorption and desorption processes, so their consentrations will be changed through either removal or addition. The objective this study is mainly to determine concentration of Pb, Cd, Cu and Zn in the dissolved phase, in suspended solid and in surface sedimens in the Estuary of Banjir Kanal Barat, Semarang. Field measurement of physical and chemical parameter were done in September 2005 in 7 station within the estuary.The results showed that the concentrations of Pb, Cd, Cu and Zn in dissolved phase were lower than those found in particles and surface sediments.